Transformation of Madrasah Financial Reports Through Sharia Accounting - Rusmini; Ardana Alfiandi (Create: Journal of Islamic Management and Business, 2025)
This study examines the implementation of Sharia accounting principles in the financial reports of Islamic educational institutions, with a case study at Madrasah Aliyah Al Qodiri 02 Krebet Gumukmas Jember. The research was conducted under the Sharia Economics Study Program, Faculty of Islamic Economics and Business, Al-Falah As-Sunniyah University (UAS) Kencong Jember. Islamic educational institutions in Indonesia, such as pesantren and madrasah, play a vital role in developing the nation’s intellectual and spiritual character. They not only impart general knowledge but also instill religious values based on Sharia principles. Using a descriptive qualitative approach, this study relies on the perspectives of participants obtained through interviews, observation, and document analysis. Data were interpreted thematically to assess the application of key Sharia accounting principles, including transparency, justice, prevention of gharar (uncertainty), prevention of riba (usury), and the management of zakat and sadaqah (charity). Findings indicate that financial reporting at Madrasah Aliyah Al Qodiri 02 is based on the General Cash Book (BKU) and the Madrasah Activity and Budget Plan (RKAM). Although the process is still manual and relatively simple, it reflects consistent efforts toward orderliness, accountability, and compliance with both government standards and Sharia values. Income from BOS funds, donations, and other sources is documented and reported periodically, while zakat and sadaqah funds are allocated to students in need. This study highlights the importance of strengthening technical guidance and human resource capacity to enhance Sharia-compliant financial reporting in Islamic educational institutions.